2016
DOI: 10.1021/acs.jpcc.6b05466
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Heat Transfer in Carbon Nanotubes - Sugar Alcohol Composite as Heat Storage Materials

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…The temperature of nanocrystal was estimated assuming heat transfer coefficient between one-dimensional nanocrystal and nanotube wall of 2 × 10 6 W/(m 2 •K), which is consistent with the results obtained for structured capsulates inside SWNTs 42,43 and the contact surface area equal to nanocrystal external surface. Calculation details are given in the Supporting Information, section S3.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…The temperature of nanocrystal was estimated assuming heat transfer coefficient between one-dimensional nanocrystal and nanotube wall of 2 × 10 6 W/(m 2 •K), which is consistent with the results obtained for structured capsulates inside SWNTs 42,43 and the contact surface area equal to nanocrystal external surface. Calculation details are given in the Supporting Information, section S3.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…The study of transport mechanisms at the nano-/micro-scale is of huge importance nowadays. In particular, nanoparticles and nanotubes demonstrate critical physical applications for nanoscale heat transfer [ 6 , 7 ]. There exist a number of models developed in a simple manner to point-like particles.…”
Section: Kozłowski Thermal Modelmentioning
confidence: 99%
“…Besides graphite or graphene, carbon nanotubes (CNTs) are more typical nano-particles in composite. Zhang et al [20] investigated on nanoscale heat transfer in composite of sugar alcohol and carbon nanotubes. It is reported that specific improvement of heat transfer depends on the material and the diameter of CNT.…”
Section: Dispersion Of High Conductive Particlesmentioning
confidence: 99%